New methods for the assessment of practical skills of nursing students - Kamińska, Alicja; Majda, Majda; Ogórek-Tęcza, Ogórek-Tęcza; Radwańska, Jadwiga (Nursing in the 21st Century, 2014)
NEW METHODS FOR THE ASSESSMENT OF PRACTICAL SKILLS OF NURSING STUDENTS Aim. The aim of this study was to evaluate the implementation of a new method of assessment of learning outcomes for nursing students – a shortened OSCE as part of the classes in Fundamentals of Nursing. Materials and methods. The study involved 298 students at their first year of full-time studies of 1st degree in Nursing at INM JU MC in Kraków. The study was performed twice at the end of the course in the skills laboratory: in January and April 2013. The course was credited by means of a shortened OSCE. That method formatted (shaped) the evaluation of the learning outcomes. After the examination, students filled in an evaluation questionnaire. The study used the method of diagnostic survey, the technique of survey questionnaire, and the research tool of proprietary evaluation survey questionnaire. Results. The method was highly praised by the majority of students as useful in the development of intellectual, practical and affective skills. In the students’ opinion, examination in the form of mini-OSCE should be evaluated favorably both in terms of content and organization. It scored high and very high in the majority of categories. Conclusions. According to the authors’ research, the scope of evaluation requires broadening and OSCE session needs multiple repetitions. The preliminary results obtained can be regarded as an attempt to objectify the new method in order to verify the effects of education among nursing students.